Nonparametric statistical inference - Gibbons, Jean Dickinson (New York: McGraw-Hill, 1971)
This textbook provides in-depth coverage of widely used nonparametric procedures, emphasizing practical application over theoretical proofs. It includes real-world examples, exercises, and step-by-step guidance on implementing these methods using statistical software like R, SAS, MINITAB, and StatXact. The book also features an appendix with essential tables for solving data-oriented problems.
Introduction and Fundamentals -- Order Statistics, Quantiles, and Coverages -- Tests of Randomness -- Tests of Goodness of Fit -- One-Sample and Paired-Sample Procedures -- The General Two-Sample Problem -- Linear Rank Statistics and the General Two-Sample Problem -- Linear Rank Tests for the Location Problem -- Linear Rank Tests for the Scale Problem -- Tests of the Equality of k Independent Samples -- Measures of Association for Bivariate Samples -- Measures of Association in Multiple Classifications -- Asymptotic Relative Efficiency -- Analysis of Count Data
3rd rev and expanded ed by J D Gibbons and Subhabrata Chakraborti. 1992 (Statistics : textbooks and monographs; 131)
Includes bibliography and index
Keywords: Statistical Inference